Assessing possible hybridization among managed Nubian ibex in North America. Issue 2 (13th December 2019) - Putnam, Andrea S.; Nguyen, Tram N.; Mott, Alison; Korody, Marisa L.; Ryder, Oliver A.
Abstract: Hybridization among closely related species is a concern in zoo and aquarium populations where unpedigreed animals are frequently exchanged with the private sector. In this study, we examine possible hybridization in a group of Nubian ibex ( Capra nubiana ) imported into the Association of Zoos and Aquariums' (AZA) Species Survival Program (SSP) from a private institution. These individuals appeared smaller in stature than adult SSP Nubian ibex and were excluded from breeding recommendations over the concern that they were hybrids. Twenty‐six microsatellites were used to rule out recent hybridization with domestic goats, Siberian ibex ( Capra sibirica ), and Alpine ibex ( Capra ibex ). We argue that natural phenotypic variation across the large geographic range of Nubian ibex may account for the small stature of the imported ibex, as private institutions may have historically acquired individuals from locations that differed from the SSP founders. However, the imported Nubian ibex appeared genetically differentiated from the SSP Nubian ibex and may represent a source of genetic variation for the managed population. Abstract : Discriminant analysis of principal components showing a lack of evidence for hybridization among the Nubian ibex individuals labeled as putative hybrids. Research Highlights: Twenty‐six microsatellites were used to rule out recent hybridization in a group of unpedigreed Nubian ibex recently imported into Association of Zoos and Aquariums' cooperative breeding program. Our study demonstrates that hybridization with domestic goats, Siberian ibex, and Alpine ibex has not occurred. It is likely the recently imported Nubian ibex' small size can be attributed to natural phenotypic variation, not hybridization. The recently imported Nubian ibex appear genetically differentiated from the managed population and may represent novel or underrepresented lineages.